2008
DOI: 10.1158/0008-5472.can-08-0101
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of Genes Affecting the RAS Pathway Is Common in Childhood Acute Lymphoblastic Leukemia

Abstract: Deregulation of the RAS-RAF-mitogen-activated protein kinase/extracellular signal-regulated kinase (ERK) kinase (MEK)-ERK signaling cascade is often caused by somatic mutations in genes encoding proteins which influence the activity of this pathway and include NRAS, KRAS2, FLT3, PTPN11, and BRAF. We report the first comprehensive mutational screen of key exons of these genes in a large cohort of unselected acute lymphoblastic leukemia (ALL) cases at diagnosis (n = 86) and in a more selected cohort at disease r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
140
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(153 citation statements)
references
References 35 publications
9
140
0
4
Order By: Relevance
“…Whether these are caused by the previous genotoxic therapy or are a consequence of inherent clonal evolution over time is unknown, and may well be impossible to clarify because ALL treatment is solely based on chemotherapy. However, it should be stressed that Case et al 28 showed that, using standard PCR and denaturing high performance liquid chromatography, RTK-RAS mutations may seem to arise at relapse; however, highly sensitive allele-specific PCR analyses nevertheless may identify them already at diagnosis, suggesting the presence of the clone that later relapsed already at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Whether these are caused by the previous genotoxic therapy or are a consequence of inherent clonal evolution over time is unknown, and may well be impossible to clarify because ALL treatment is solely based on chemotherapy. However, it should be stressed that Case et al 28 showed that, using standard PCR and denaturing high performance liquid chromatography, RTK-RAS mutations may seem to arise at relapse; however, highly sensitive allele-specific PCR analyses nevertheless may identify them already at diagnosis, suggesting the presence of the clone that later relapsed already at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The present finding that deletions of SPRED1 are recurrent and that they provide a negative prognostic impact in BCP ALL is clinically important, not least considering that SPRED1 is part of MAPK signaling and that inhibitors of this pathway currently are undergoing clinical trials and hence may be novel therapeutic options. 24 The multivariate analyses strongly indicated that IKZF1 deletions were the strongest independent risk factor for poor outcome ( Table 4). The transcription factor IKZF1 is essential for B-cell development, with loss of IKZF1 leading to arrest of lymphoid differentiation.…”
mentioning
confidence: 94%
“…22,23 SPRED1 has previously not been implicated in ALL but mutations of other RTK-RAS genes, such as FLT3, KRAS, NRAS, and PTPN11, have been reported to be enriched at ALL relapses. 16,24 The only genomic imbalance significantly associated with relapse (Table 2) was del(6)(p22.2p22.2), involving the histone genes HIST1H2BD and HIST1H1E in the smallest overlapping region. HIST1H2BD and HIST1H1E are part of the nucleosome structure of the chromosomal fiber and essential for cytokinesis.…”
mentioning
confidence: 99%
“…In particular we tested for a BCR-ABL1-like expression signature including specific targetable fusions, 4 performed phospho-flow cytometry for targetable kinase activity; low-density genomic analysis by multiplex ligation-dependent PCR (MLPA); and screened for activating RAS or JAK mutations. 4,5 Twenty non-irradiated, immune-deficient, NOD/SCID/IL-2 receptor gamma − / − (NOD.Cg-Prkdc scid Il2rg tm1Wjl /SzJ, NSG) mice were inoculated by tail vein injection 8 days after the 2nd relapse with 2 × 10 6 BM cells (from the 2nd relapse) to establish the PDX. 6 1.0E-01 Following a 2nd course of topotecan, MRD was undetectable 119 days after the 2nd relapse and remained negative until 259 days after the 2nd relapse.…”
mentioning
confidence: 99%
“…MLPA analysis showed heterozygous deletion of JAK2 exon 23, homozygous deletion of CDNK2A and B, and diploid copy number for EBF1, IKZF1, PAX5, ETV6, BTG1, RB1 and CRLF2 (Supplementary Table S3). The targeted analyses were negative for the known KRAS or NRAS mutations 5 and negative for fusions and mutations in JAK1 and JAK2. 4 Gene expression profiling for a BCR-ABL1-like signature showed no overexpression of CRLF2, PDGFRB, ABL1, ABL2 or EPOR.…”
mentioning
confidence: 99%